POLITIK ISLAM INDONESIA SEBAGAI SENTRUM PERDAMAIAN DUNIA - Ardhani, Hasbi; Basriadi, Basriadi; Hamroni, Hamroni; suarjana, Suarjana (STIS Darussalam Bermi, 2022)
This study was conducted to determine the political Islam of Indonesia position in the world, it could become a center for world peace. Cause of the socio - political situation of Islam has recently faced what is called a real and inevitable paradox, accompanied by its status as the largest religion in Indonesia. In previous era, Islam managed to come out as a winner with a very real labeling and Islamic identity, other forces were unable to stem it, avoiding fear of defeat, let alone groups. But in reality, none of them last. In the socio - political dynamics of Indonesia, it turns out that Islamic politics is not necessarily easy to be a winner in political contestation in the case area and legal dimensions of Indonesia. This study is qualitative - descriptive based on field research, with historical approaches and political sociology. In conclusion, the Islamic ummah in Indonesia must be able to re-construct, re-solve and re-contextualize Indonesia's socio - political transformation. The exclusive nature of Indonesian Islam will in fact make it worse off because it is unable to withstand all changes. If the nature of inclusion becomes the main identity of Indonesian Muslims as a whole, political Islam in Indonesia will become the center of peace in the world. No country is as complex as Indonesia, in which various ethnicities, races, cultures, languages, religions and so on. But what other countries worry about Indonesia is in fact disproved. Indonesia has been able to survive until now with various differences, this is because of the Islamic figures in Indonesia. Although sometimes or even often religious issues are played only to gain power.